Marketing mix effects on private labels brand equity - Carmen Abril Barrie; Belén Rodriguez-Cánovas (European Journal of Management and Business Economics (EJM&BE), 2016)
The present study explores some marketing mix effects on private labels brand equity creation. The research aims to study the effect of some elements under retailer's direct control such as in-store communications, in-store promotions and distribution intensity as well as other general marketing mix levers such as advertising, perceived price, and monetary promotions. The results indicate that the most efficient marketing mix tools for private label brand equity creation are private labels in-store communications, private labels distribution intensity and the perceived price. These results highlight the importance of the store as a key driver for the private labels brand equity creation. As opposed to manufacturer brands we find no effect of advertising on the private labels brand equity and an opposite effect of the perceived price. This study is a pioneering contribution in the domain of private labels brand equity research exploring a more comprehensive and in-store specific set of marketing mix initiatives as sources of brand equity. The results suggest important implications for retailers when managing their own brands.
Keywords: M31; M37; 650; Brand equity; Distribution; In-store communication; Private labels; Store brands